The Association of Complementary Therapy Use with Prescription Medication Adherence among Older Community-Dwelling Adults - Effoe, Valery S. (J Appl Gerontol, 2015)
Medication adherence is a major health concern, particularly among older adults who have one or more chronic conditions. We examined the association between complementary therapy use and medication adherence among older community-dwelling adults. In a bi-ethnic sample of 165 adults aged 65 years and older, anthropometric variables, data on chronic medical conditions, and medication use were assessed. Medication adherence was modeled as a score (<50%, 50%–75%, and >75%) and complementary therapy use was categorized as a binary variable. Over half of participants (50.3%) were female, and 47.3% were African American. Complementary therapy use was prevalent (87.9%) and did not differ by sex, ethnicity, income, and educational attainment. Medication adherence score was > 75% in 84.8% of complementary therapy users and 80.0% of non-users (p = 0.61). Despite a high use of complementary therapy in this population, there was no apparent association with low medication adherence.